Guinea : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses the Staff-Monitored Program (SMP) for Guinea. Agreement in principle was reached on the SMP from April 2005 to March 2006. The program would support the authorities' efforts in restoring macroeconomic stability and establish a track record of policy implementation to pave the way for a new Poverty Reduction and Growth Facility arrangement and subsequently reach the completion point under the Heavily Indebted Poor Countries Initiative. The program also includes structural reforms targeted to support macrostabilization efforts and to lay the basis for stronger and sustained economic growth.